Sistem Pendukung Keputusan Penentuan Prioritas Proyek Untuk Implementasi IT Strategic Planning Universitas Atma Jaya Makassar - Tungadi, Astrid Lestari (TEMATIKA, Journal of Informatics and Information Systems, 2017)
A university needs IT strategic planning to be able to guide the future development of the university, one of them is Atma Jaya University of Makassar. The IT Implementation at AtmaÂ Jaya University of Makassar is currently still minimal because it has not utilized information technology well and thoroughly for operational purposes. This is due to the absence of IT strategic planning for the long term. The previous research has designed IT strategic planning using the Mobile Enterprise Architecture Framework. The documentation results from IT strategic planning have some recommendations of IT projects that can be implemented. The priority selection of IT project becomes very important in achieving IT strategic planning that has been designed. This research applies Analytical Hierarchy Process and utilizing Expert Choice tools to get priority from 20 recommended IT projects that related with IT strategic planning. There are 7 criteria of IT project implementation that is obtained from Head of BAPSI UAJM. The result of this research shows that IT project which is the main priority to be implemented is the Development of Student Portal and Lecturer with the priority scale of 0.109 and the lowest priority IT project is the Procurement of LAN Cable (0.011) because the network infrastructure in UAJM is currently sufficient to support the designed IT strategic planning.Keywords: IT strategic planning, project priority, Decision Support System, Analytical Hierarchy Process